The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201500896
|View full text |Cite
|
Sign up to set email alerts
|

Direct Aromatic CH Trifluoromethylation via an Electron‐Donor–Acceptor Complex

Abstract: A novel electron-donor-acceptor (EDA) complex-mediated direct C-H trifluoromethylation of arenes with Umemoto's reagent has been developed. This transformation has been enabled by an unprecedented EDA complex formed by Umemoto's reagent and an amine, which was supported by experiments and theoretical calculations. The radical-based methodology presented here allows to access highly-functionalized trifluoromethyl arenes in up to 81 % chemical yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 97 publications
2
37
0
Order By: Relevance
“…[6] In particular, pioneering studies by Melchiorre and co-workersh ave shown that photoexcited electron donor-acceptor (EDA) complexes have significant potential to enable CÀCbond formation under mild metal-and peroxide-free conditions. [7,8] Strategies using these complexes in synthesis are typicallyo perationally simple and can be readily performed with simple organic precursors. For example, electron-rich indole donors can be photochemi-cally alkylated with highly electron-deficient dinitrobenzyl bromide acceptors (Scheme 1a).…”
mentioning
confidence: 99%
“…[6] In particular, pioneering studies by Melchiorre and co-workersh ave shown that photoexcited electron donor-acceptor (EDA) complexes have significant potential to enable CÀCbond formation under mild metal-and peroxide-free conditions. [7,8] Strategies using these complexes in synthesis are typicallyo perationally simple and can be readily performed with simple organic precursors. For example, electron-rich indole donors can be photochemi-cally alkylated with highly electron-deficient dinitrobenzyl bromide acceptors (Scheme 1a).…”
mentioning
confidence: 99%
“…Angewandte Chemie known to form EDAc omplexes with species other than styrenes. [18] We observed that the glycosyl donor 23 (Scheme 2) did not generate ayellow color upon dissolution with Umemotos reagent. Further,s pectrophotometry showed little or no evidence for the EDAcomplex (see the Supporting Information).…”
mentioning
confidence: 88%
“…In 2010 Sodeoka and co‐workers disclosed an efficient Cu‐catalyzed electrophilic trifluoromethylation featuring Togni reagent II as the CF 3 source for the modification of a vast array of indoles, including the Trp derivative Ac‐Trp‐OMe . More recently, the radical trifluoromethylation of Ac‐Trp‐OMe has been achieved by using Ummemoto reagents as practical sources for the production of the corresponding radical trifluoromethyl species by reaction with the electron‐donor N ‐methylmorpholine (NMM) or under photo‐irradiation conditions . Likewise, the organic semiconductor mesoporous graphitic carbon nitride (mpg‐CN) has proven a sustainable, yet highly efficient photocatalyst for the C2‐trifluoromethylation of Boc‐Trp‐OEt with both Langlois reagent and CF 3 SO 2 Cl .…”
Section: Trifluoromethylation Of Peptidesmentioning
confidence: 99%